Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa - Ellen Milenia; Johny Subarkah; Suprihati Suprihati (ITB AAS INDONESIA, 2023)
This study aims to determine the effect of the competence of village fund management apparatus, internal control systems, and the use of information technology on village fund management accountability. This research is a quantitative research with a questionnaire. The subject of this research is the village administration in Kartasura District, Sukoharjo Regency. The population in this study was all village officials in Kartasura District, totaling 111 officers and the sample used was taken from the slovin formula as many as 87 respondents. The data analysis technique used descriptive statistics, validity tests, and reliability tests. Classical assumption test using normality test, multicollinearity test and heteroscedasticity test. And testing the hypothesis using multiple linear regression analysis, F test, t test, and test the coefficient of determination. The results showed that simultaneously the competence of the village fund management apparatus, internal control system, and the use of information technology had a significant effect on the accountability of village fund management. While partially the competence of the village fund management apparatus does not have a positive and significant effect on the accountability of village fund management, as well as the internal control system and the use of information technology have a positive and significant effect on the accountability of village fund management partially. Keywords: competence of village fund management apparatus, internal control system, utilization of information technology, accountability of village fund management.